How to Understand Earnings Management across Identification of Discretionary Accounting and Financial Variables: The Case of Tunisian Companies (Global Journal of Management and Business Research, 2019)
This research work is part of the investigation of the determinants that taint the quality of accounting information disclosed on the Tunisian financial center and the incentives that enact Accounting policies conducted by managers and which are related to financial failure. To better understand this dilemma (manipulation of accounting data -financial failure) we have adopted an econometric approach allowing us to distinguish the discretionary accruals characterizing companies with high financial profitability from those specific to companies with low financial profitability and this, based on the postulate of the positive theory of accounting which considers that managers of companies experiencing difficulties make accounting choices to artificially embellish the published net result.
Keywords: earnings management - discretionary accruals - financial failure